The Prophet and the Woman Who Shatters and Heals - Murray, Joan L. (Journal of religion and health, 1997)
What does the story of Jesus's anointment by a woman say about pastoral care? This is a case study which addresses pastoral care in a communal and medical setting. Jesus both challenges and comforts in His response to those at table. The case study raises for reflection the question of whom I am at table with and what the answer says about me.